2018
DOI: 10.1186/s12879-017-2892-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of Mycobacterium fortuitum pulmonary infection presenting with migratory infiltrates: a case report with microbiological analysis

Abstract: BackgroundPresence of Mycobacterium fortuitum in respiratory tracts usually indicates mere colonization or transient infection, whereas true pulmonary infection occurs in patients with gastroesophageal disease. However, little is known about the diagnostic indications for true M. fortuitum pulmonary infection and the natural history of the disease.Case presentationA 59-year-old man was referred to our hospital for treatment against M. fortuitum pulmonary infection. Fifteen years before the referral, he underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
190
9
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(228 citation statements)
references
References 25 publications
27
190
9
2
Order By: Relevance
“…This organism is a rapidly growing mycobacteria initially isolated and characterized in 1938 from a stomach lavage specimen. 42 These findings are in accordance with another report from various parts of the world, which showed the M. fortuitum is one of the most common actinomycetes species isolated from clinical samples. 35 In the current study, M. fortuitum was isolated from lung secretion, abscess, and wound of cancerous patients.…”
Section: Discussionsupporting
confidence: 92%
“…This organism is a rapidly growing mycobacteria initially isolated and characterized in 1938 from a stomach lavage specimen. 42 These findings are in accordance with another report from various parts of the world, which showed the M. fortuitum is one of the most common actinomycetes species isolated from clinical samples. 35 In the current study, M. fortuitum was isolated from lung secretion, abscess, and wound of cancerous patients.…”
Section: Discussionsupporting
confidence: 92%
“…The type, amount, frequency and duration of oil use documented in the selected studies varied widely; and may partly explain the heterogeneous clinical-radiological pattern of paediatric ELP that makes it indistinguishable from other causes of persistent pneumonia or diffuse lung disease in children. NTM disease in patients with ELP is an important comorbidity that is postulated to be favored by the lipophilic environment, and is a finding that is consistent with previous experimental studies [48] and literature in adults [49,50]. Supportive management particularly antibiotic treatment was the most common treatment offered to children with ELP.…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, a study conducted in Taipei concluded that the risk of TB recurrence among persons smoking >10 cigarettes/day was twice that of nonsmokers and exsmokers [46]. Another study performed in the United Kingdom found that smoking was a predictive factor for TB recurrence [47]. In Yemen, patients smoking > 20 cigarrettes/day had a higher risk of TB recurrence than those smoking <20 cigarrettes/day [48].…”
Section: Discussionmentioning
confidence: 99%